Production evaluation of Lentinula edodes Pegler fungi in synthetic logs based on agricultural wastes (2007)
The cultivation of Lentinula edodes, edible, medicinal mushroom and commonly called shiitake, was evaluated in synthetic blocks in order to take advantage of different agroindustrial wastes not studied so far quantitatively, and that represent an environmental problem for some companies. 55 different combinations of substrates were made using two agroindustrial residues (cocoa husk and cotton motile), a timber supplement (oak chip), a nitrogen source (wheat bran), a pH controller (CaCO3) and a stimulator growth (CaSO4). It was found that the substrate formulation has a great effect on the colonization time of the block (P <0.05), the oak chip being an essential element for the reduction of the colonization time. Additionally, it was found that cocoa husk is not a good supplement for macromycete production. The treatments that provided better conditions for the formation of fruiting bodies contained 75% oak chip in combination with wheat bran (20-25%) or cotton motose (25%). Depending on the treatment evaluated, biological efficiencies were obtained between 5.3 and 21.5%, pylorus sizes between 4.7 and 9.3 cm for the first harvest, colonization precocities between 69 and 125 d ´ıas, with C / N ratios higher than 110 and nutritional qualities higher than those reported by other researchers.